KONTEKSTUALISASI HUKUM KEADILAN DALAM QISHAS - Muchsin, Agus (DIKTUM: Jurnal Syariah dan Hukum, 2011)
This article describes the problem in Qishas contextualisation Justice. Assessment results obtained from the understanding that the term "Adala", which is aplication used for interpretation of justice, in the mentioned 28 times in the Koran. The word, describes a situation that is straight. Called Straight specifically because it meaningful determination of the law correctly. In terms of Islamic studies is examined more specifically by Mutazila as one school of thought that maintains the justice of God. In Islamic criminal law, sanctions the world divided into two kinds, namely: the first based on texts in the form of Qisas, diyat and had. Second, the government left to the discretion of tazir. Qishas fiqhi language more commonly used as a punishment qishas threatened with sanctions or disciplinary action taken as a reply in kind. Meanwhile, in view of the West, Islamic law is too cruel and inhumane even been blamed for something that is very unfair, because the children worth it unable to provide a deterrent effect on the perpetrators, and provide no assurance that qishas more effectively than other punishments severe. This assumption is refuted by the phenomenon in several Western countries, there are people who are not satisfied with the legal sanction given so that it appears not believe the attitude of law enforcement and legal materials.